Kinetics of the homogeneous hydrogenation of avermectins catalyzed by RhCl(Ph3P)3 complexes - Zgolicz, Patricia Daniela (2005)
The kinetics of the hydrogenation of avermectins B1a and B1b catalyzed by RhCl(Ph3P)3 complexes was studied in a temperature range of 298–328 K at 275.7 kN m2, using catalyst loading in the range of 0.75–7.25 wt.% with respect to the avermectins in toluene solution. The effects on the hydrogenation rate of the catalyst, avermectins, and hydrogen concentrations were determined under complete induction time suppression and without catalyst deactivation. Rate equations were developed for various kinetic schemes on the basis of the main steps suggested by Wilkinson for simple oleﬁn hydrogenation and ﬁtted to the experimental data. A statistical analysis of regression using three plausible mechanisms of reaction allows a discussion on the adequacy of the models to approach the observed half-order reaction with respect to the catalyst loading and ﬁrst-order to avermectins and hydrogen concentrations. A reaction mechanism featuring non-extensive simple dissociation of the catalyst precursor and reaction pathway along the hydride route with the rate-determining oleﬁn coordination step proved fair enough to describe the hydrogenation of this macrocyclic lactone. The physical reasonability of the equilibrium and kinetic parameters was also discussed.